Microfacies Architecture and Stratigraphic Development of the Yamama Formation, Southern Iraq - Al Mafraji, Taisir Ghanem Zaki; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2019)
The Yamama Formation belongs to the late Berriasian-Aptian succession, which was deposited during the Lower Cretaceous period within the main shallow marine depositional environment.Petrographic study and microfacies analysis enabled the recognition of six main microfacies for three association facies. These are the Semi-restricted, Shallow open marine and Shoal environments. The study succession represents deposition of three third order cycles, these cycles where deposited during successive episodes of relative sea level rises and still stand.The presence of shoal association facies (oolitic packstone microfaces) between the Sulaiy and Yamama formations refer to continue the deposition during the same stage, and may suggest the end of Sulaiy Formation was maximum flooding surface (mfs). The first stage started with occurrence of the shallow open marine association facies underlain by semi-restricted association and then shoal association facies.There are three cycles of this sequence consistently in the south of the study area, so that it continues to the lower part of the Ratawi Formation to be the upper contact of the Yamama Formation of a conformable and continuous in sedimentationTo the north of the study area (near of Rf-1 and Hf-5 wells) the shoal association was only shown once at the bottom of the Yamama Formation and these cycles to became unclear. This suggest that the paleo-high was developed to the south of studied area, while the open sea was characterized the northern part.